On the Question of Church Slavonic Vocabulary in the Belarusian Dialects - Шакун, Надзея (Slavistica Vilnensis, 2018)
[full article, abstract in Belorussian; abstract in Lithuanian and English]The article focuses on a review of the theoretical principles of search, further analysis and interpretation of the ways and time of Church Slavonic vocabulary loan to the Belarusian dialects, according to the data of the Belarusian dialect dictionaries of the 19th and 20th centuries, as well as some ethnographic works. The article presents a brief overview of how deeply this issue is studied in modern Slavic studies in general and in Belarus in particular. There are proposed ways of highlighting the peculiar markers of the “oldness” of loanwords. As a practical material, the most specific examples of Church Slavonic words, used in Belarusian dialects, are shown, accompanied by comments on possible ways of loaning them into the dialects. The author of the article disputes the stereotype that the Belarusian national language, in particular in its dialect form, performs the poorest influence of the Church Slavonic literary tradition against the background of the rest of Slavonic languages, therefore it contains the insignificant part of Church Slavonic vocabulary.
Keywords: Cyrillo-Methodian language heritage, Church Slavonic lexis, Belarusian dialects, nonpleophonic forms in the Belarusian dialects